Role of laboratory chemosensitivity testing in the selection of cancer chemotherapy for individual patients. Issue 5 (May 1981) - Selby, P J; Raghavan, D
Abstract : Recently several assays have been developed which allow the growth of colonies from cell suspensions prepared from human tumour biopsy specimens. It has been suggested that such assays will provide a reliable means of measuring the chemosensitivity of human tumours for predicting the response to treatment in patients. We have briefly reviewed the previous, largely unsuccessful, attempts at chemosensitivity testing and the potential place of the new assays. The measurement of the survival of clonogenic tumour cells after cytotoxic treatment probably reflects to some extent the survival of cells which in vivo are capable of proliferating to repopulate and regrow the tumour. This endpoint therefore has advantages over alternatives that do not directly measure reproductive cell death, and the assays also have the advantage of suppressing the growth of many non-malignant cells found in tumours. However, technical problems such as the preparation of cell suspensions and the artificial nature of the drug exposure phase of the assays have not been completely overcome and the plating efficiencies remain low in most systems. Work with model systems such as human tumour xenografts tends to support the usefulness of the assays but also highlights some difficulties. Clinical studies of chemosensitivity testing are in progress and initial results are encouraging but inconclusive.